Pengembangan Website Fakultas Teknik Universitas Hamzanwadi Berbasis Progressive WEB APP (PWA) - Iwan Aslan; Hariman Bahtiar; Aris Sudianto (Fakultas Teknik Universitas Hamzanwadi, 2022)
The Hamzanwadi University Faculty of Engineering website is an online news media that provides comprehensive information about the Hamzanwadi University Faculty of Engineering. However, in an effort to improve the quality of accessing this information, the website needs to be improved. By implementing Progressive Web Apps (PWA) technology, it is hoped that it can be a solution to existing problems. By implementing PWA technology, it will have a significant impact on the Faculty's website, when compared to before. Of course, with the application of PWA technology, the loading process on the website will be much lighter, faster, and more time efficient and open when not connected to the internet or offline.